Molecular identification of Saint Louis encephalitis virus genotype IV in Colombia (2015)
ABSTRACT: Saint Louis encephalitis virus (SLEV) is a member of the Japanese-encephalitis virus serocomplex of the genus Flavivirus. SLEV is broadly distributed in the Americas and the Caribbean Islands, where it is usually transmitted by mosquitoes of the genus Culex and primarily to birds and mammalian-hosts. Humans are occasionally infected by the virus and are dead-end hosts. SLEV causes encephalitis in temperate regions, while in tropical regions of the Americas, several human cases and a wide biological diversity of SLEV-strains have been reported. The phylogenetic analysis of the envelope (E) protein genes indicated eight-genotypes of SLEV with geographic overlap. The present paper describes the genotyping of two SLEV viruses detected in mosquito-pools collected in northern Colombia (department of Cordoba). We used reverse transcription-polymerase chain reaction to amplify a fragment of the E-gene to confirm the virus identity and complete E-gene sequencing for phylogenetic analysis and genotyping of the two-SLEV viruses found circulating in Córdoba. This is the first report of SLEV genotype IV in Colombia (Córdoba) in mosquitoes from a region of human inhabitation, implicating the risk of human disease due to SLEV infection. Physicians should consider SLEV as a possible aetiology for undiagnosed febrile and neurologic syndromes among their patients who report exposure to mosquito-bites.